BENTUK DAN FUNGSI KODE DALAM WACANA KHOTBAH JUMAT (Studi Kasus di Kota Surakarta) - Kundharu Saddhono (Adabiyyāt: Jurnal Bahasa dan Sastra, 2012)
This study aims at describing the discourse of Friday sermons in the city of Surakarta. This study is a sociolinguistic study with qualitative research method. The language based code shows Indonesian language is used dominantly because the object of study is in Surakarta. Arabic is widely used because the Friday sermons are one kind of worships in Islam. Javanese language is used because of the speech location and cultural backgrounds. English only slightly appears and is influenced by the speakers’ background. The code based on the variations can be divided into the standard and non standard languages. Intra-sentential code switchings take the forms of words, reduplication, word repetitions, and phrases. This is due to attitudinal and linguistic factors. Inter-sentential code switchings are permanent and temporary. The determining factors are speakers, interlocutors, topics or subject matters, special speech functions/ends, and changes in circumstances. The functions of code switching in the Friday sermons are to express gratitude, purify God, glorify God, honor someone, express amazement, prohibit, sound prestigious, express permission, beg for forgiveness, beautify utterances, change the subject, pray for someone, declare an appointment, mention terms, express doubts, and regret something.